Etiological profile of febrile thrombocytopenia in children aged <12 years in a tertiary care centre - Moluguri, Sony; Tanneru, Shreya; Thanda, Prasad; Thomas, Suresh R. J. (International Journal of Contemporary Pediatrics, 2023)
Background: Febrile thrombocytopenia is platelet count <1,50,000/mm3 associated with fever irrespective of age and gender. There is an increasing trend in the incidence of febrile thrombocytopenia with varied etiology. Though infections are the most common cause in tropical countries like India, sometimes non-infectious conditions like primary haematological disorders and malignancies can also present as febrile thrombocytopenia. Hence it is essential for the treating physicians to be fully aware of etiological factors for febrile thrombocytopenia and how to approach to the condition. Methods: A hospital based observational study done at Kamineni Institute of Medical Sciences during the study period October 2020 to December 2021 by collecting and analysing details of 100 patients between 1 month-12 years of age who presented with fever and thrombocytopenia at admission. Patients on drugs causing thrombocytopenia were excluded from the study. Results: Majority of the cases (51%) belonged to the age group of 1-6 years. Out of 100 subjects, 60% of them had dengue fever, 12% of cases had malaria and 10% of cases had enteric fever. Bleeding manifestations were seen in 12% of cases and blood product transfusion was done in 30% of the cases. 98% of cases had recovered and 2 deaths were reported. Conclusions: Febrile thrombocytopenia is a common clinical presentation in children. Majority of the dengue cases responded well to treatment given as per WHO guidelines. In most of the other infections, thrombocytopenia was transient and asymptomatic with lesser severity and resolved with the treatment of underlying condition.